Genotype-phenotype correlations of marfan syndrome and related fibrillinopathies: Phenomenon and molecular relevance - Chen, Ze-Xu; Jia, Wan-Nan; Jiang, Yong-Xiang (Frontiers in Genetics, 2022)
Marfan syndrome (MFS, OMIM: 154700) is a heritable multisystemic disease characterized by a wide range of clinical manifestations. The underlying molecular defect is caused by variants in the FBN1. Meanwhile, FBN1 variants are also detected in a spectrum of connective tissue disorders collectively termed as ‘type I fibrillinopathies’. A multitude of FBN1 variants is reported and most of them are unique in each pedigree. Although MFS is being considered a monogenic disorder, it is speculated that the allelic heterogeneity of FBN1 variants contributes to various manifestations, distinct prognoses, and differential responses to the therapies in affected patients. Significant progress in the genotype–phenotype correlations of MFS have emerged in the last 20 years, though, some of the associations were still in debate. This review aims to update the recent advances in the genotype-phenotype correlations of MFS and related fibrillinopathies. The molecular bases and pathological mechanisms are summarized for better support of the observed correlations. Other factors contributing to the phenotype heterogeneity and future research directions were also discussed. Dissecting the genotype-phenotype correlation of FBN1 variants and related disorders will provide valuable information in risk stratification, prognosis, and choice of therapy.